2008
DOI: 10.1002/yea.1642
|View full text |Cite
|
Sign up to set email alerts
|

Coding repeat instability in the FLO11 gene of Saccharomyces yeasts

Abstract: In Saccharomyces yeasts, the FLO11 gene encodes an adhesin involved in filamentation, invasive growth, flocculation and adherence to solid surfaces. In wild Saccharomyces flor yeasts, a particularly expanded FLO11 allele also confers to these yeasts the ability to float under stressing liquid environments. We report here that, under optimal laboratory conditions, the repeats domain of the FLO11 gene in these wild yeasts is extremely unstable. Changes in length in the FLO11 coding repeats domain affected Flo11p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 36 publications
5
46
0
Order By: Relevance
“…In these transformants, as the gene length increased, so did the weight of the biofilm. The same results were obtained by Fidalgo et al (2008), who showed the phenotypic effects of different alleles of FLO11 in flor/laboratory hybrids of S. cerevisiae. However, to conclude that the expansion and contraction of repeated sequences allow natural populations to rapidly adapt to a fluctuating environment, it is necessary to study the phenotypic effects of the different FLO11 alleles in their specific genetic backgrounds.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In these transformants, as the gene length increased, so did the weight of the biofilm. The same results were obtained by Fidalgo et al (2008), who showed the phenotypic effects of different alleles of FLO11 in flor/laboratory hybrids of S. cerevisiae. However, to conclude that the expansion and contraction of repeated sequences allow natural populations to rapidly adapt to a fluctuating environment, it is necessary to study the phenotypic effects of the different FLO11 alleles in their specific genetic backgrounds.…”
Section: Discussionsupporting
confidence: 73%
“…It has been reported that in the same genetic background, differences in the lengths of repeated sequences in the FLO11 gene correlate with variations in the intensities of some FLO11-associated phenotypes (Fidalgo et al, 2008 The same analysis regarding FLO11 alleles and FLO11-dependent phenotypes was carried out considering different genetic backgrounds. To this end, Spearman's correlation coefficients (r) were calculated by considering the length of FLO11 repeated sequences and mat formation, adherence to plastic, biofilm-forming ability and hydrophobicity of the 14 flor wild strains that were homozygous at the FLO11 locus.…”
Section: Flo11 Is Highly Polymorphicmentioning
confidence: 99%
“…Among these individuals (n = 30), we identified a single locus that was nearly fixed for the YJM allele ( Figure 3A, top), which was located on chromosome IX and overlapped FLO11. FLO11 is known to harbor extensive functional variation across yeast isolates in both its coding and noncoding regions (Fidalgo et al 2006(Fidalgo et al , 2008. To test for functional variation at FLO11 in the BYxYJM cross, we separately replaced the coding and noncoding regions of FLO11 in Segregant 2 with the BY alleles ( Figure S1; see also Materials and Methods).…”
Section: Multiple Architectures Of Flo8-independent Invasion In Ethanmentioning
confidence: 99%
“…The loss or gain of FLO11D allele events can be explained by the dendrogram, which suggested that the FLO11D allele originated from a single origin and that sequence alteration in the third FLO11D allele occurred in Z3 after its acquisition. In S. cerevisiae, it has been reported that the length and type of repetitive units in the Flo11p coding repeats domain affect the Flo11p-associated functions, including cellular hydrophobicity (Fidalgo et al 2006;Fidalgo et al 2008;Zara et al 2009); however, the relationship between its functions and the copy number of the FLO gene itself has not been elucidated. To investigate this relationship, we measured the cellular hydrophobicity of FLO11D mutants in Z3.…”
mentioning
confidence: 99%
“…The latter domain is also referred to as a domain with intragenic tandem repeats. The variation in the intragenic repeat number and/or the distribution of the different repetitive units provides a functional diversity of the cellsurface antigens that allows rapid adaptation to the environment (Verstrepen et al 2005;Fidalgo et al 2006Fidalgo et al , 2008Zara et al 2009). However, the relationship between adaptation and the copy number of the FLO gene itself, but not the number of the intragenic repeat units, has not been investigated.…”
mentioning
confidence: 99%